1999
DOI: 10.1007/s007950050024
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-induced apoptosis in the mitotic phase: electron microscopic and cytochemical studies of human leukemia cells

Abstract: We induced apoptosis in cells of the human leukemia cell line HL-60 using an antitumor agent, docetaxel (Taxotere), and investigated apoptosis in various aspects using in situ end-labeling (ISEL) of DNA, DNA fragmentation assay, flow cytometry, and electron microscopy. Because it inhibits depolymerization of tubulin, docetaxel is thought to arrest the cell cycle at the mitotic stage and to exert an antitumor effect. In this study, accumulation of docetaxel-treated cells at the G2/M phase was detected using flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Docetaxel induced microtubule damage results in a marked and prolonged G 2 -M arrest and subsequent apoptosis (40). Flow cytometric analysis of docetaxel-treated cells therefore exhibits an increase in the number of cells in the G 2 -M phase, suggesting a G 2 -M block and an increase in sub-G 0 -G 1 phase, indicating the hypodiploid or apoptotic cells.…”
Section: Discussionmentioning
confidence: 98%
“…Docetaxel induced microtubule damage results in a marked and prolonged G 2 -M arrest and subsequent apoptosis (40). Flow cytometric analysis of docetaxel-treated cells therefore exhibits an increase in the number of cells in the G 2 -M phase, suggesting a G 2 -M block and an increase in sub-G 0 -G 1 phase, indicating the hypodiploid or apoptotic cells.…”
Section: Discussionmentioning
confidence: 98%
“…First, antagonism between imatinib and docetaxel may occur because imatinib mesylate may arrest tumor cells at the G 0 -G 1 checkpoint through inhibition of PDGFR␣ and the downstream PI3K/AKT pathway 31 ; this may compromise the antitumor effects of docetaxel, which works during M phase. 32,33 Second, p-glycoprotein (MDR-1), an ATP-binding cassette (ABC) transport protein B1, has both docetaxel and imatinib as substrates and is implicated in resistance to both agents. 34,35 The ABCB1 gene is strongly induced by docetaxel in resistant A549 cell lines 35 possibly through activation of pregnane X receptor pathway 36 ; and imatinib resistance has also been linked to ABCB1 induction in leukemic cell lines.…”
Section: Proposed Mechanisms Of Resistance and Antagonismmentioning
confidence: 99%
“…Docetaxel is the standard of care for men diagnosed with AIPC [1] . Docetaxel binds to the β-tubulin subunit, causing stabilization of microtubules, which leads to mitotic arrest and subsequent apoptosis [2] . Docetaxel has been administered to men with AIPC in clinical trials, where it has been found to prolong survival in men with this disease [3] .…”
Section: Introductionmentioning
confidence: 99%